Dietary ascorbic acid and betaine improve stress responses, testosterone levels and some sexual traits in male Japanese quails during the dry season. (26th July 2021) - Michaelis, Martin; Egbuniwe, Ifeanyichukwu Chukwuemeka; Uchendu, Chukwuka Nwocha; Obidike, Ikechukwu Reginald
Abstract: The experiment investigated the effects of dietary ascorbic acid and betaine stress responses, serum testosterone levels, and some sexual traits in male Japanese quails during the dry season. A total of 240 male Japanese quails (14 days old) were used and randomly assigned to four groups, each group has three replicates ( n =  20). Birds in treatment groups were fed ascorbic acid (AA); betaine (BET); and AA + BET in their diets, whereas the control birds were fed only basal diet. Environmental conditions were predominantly outside thermoneutral zone for Japanese quails. Dietary AA ± BET increased ( p  < .05) serum catalase, reduced glutathione and testosterone, but lowered ( p  < .05) cortisol levels when compared with control group. Supplemental AA, BET, or AA + BET enhanced ( p  < .05) cloacal gland size and sexual traits. In conclusion, dietary AA and BET improved stress responses, serum testosterone levels, and some sexual traits in male Japanese quails during the dry season.